Profesor Camilleri i pan Caravaggio. Multimodalne studium twórczości i psychozy - Olkusz, Ksenia (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Multimodal techniques (meaning the use of narrative modes signalised by various typographies etc.) enable a fuller presentation of Caravaggio’s mental dysfunction (in the novel the focalizing role is performed by, among others, the notes of the painter who is falling into obsession and madness – it is these that form his internal storyworld). Confrontation with the journalistic account, provided by the alter ego of the very author of the novel (so called sylleptic narrator) – that is the second level of narration – constitutes the modal frame for the presentation of the artist’s fate and contributes to showing the mental state of Caravaggio who is obsessed with “black sun” (this obsession might be the source of the chiaroscuro technique), and who sees in hallucinations his own severed head. This way, Camilleri creatively exploits the motif of decapitation, found in Caravaggio’s paintings, following many research studies showing that the heads found in the paintings could have been the painter’s self-portraits and expressions of his expiation. This context is supplemented by reproductions of Caravaggio’s paintings, which are embedded in the narration and “commented upon” in his fictional journal, thus constituting yet another layer registering (and illustrating) what takes place in the artist’s mind.